Crystal Chemistry of the Antibiotic Doripenem. Issue 11 (17th September 2014) - Colombo, Valentina; Masciocchi, Norberto; Palmisano, Giovanni
<x xml:space="preserve">Abstract</x> Doripenem, an ultrabroad spectrum‐injectable antibiotic belonging to the wide class of carbapenem beta‐lactams, is commonly marketed as powders of a pure monohydrate phase. Here, we have selectively prepared another hydrated phase (a dihydrate) and determined the crystal structure of both forms by state‐of‐the art powder diffraction methods. Both phases crystallize in the monoclinic P21 space group, and, to some extent, are structurally related. Moreover, by using variable temperature diffractometric analyses, we also discovered a crystalline anhydrous form of doripenem, the structure of which (with two crystallographically independent molecules in the monoclinic P21 space group) remains so far unknown. The thermal interconversion among these phases was further studied by thermogravimetry, differential scanning calorimetry, and thermodiffractometric analyses, and their (metric or stereochemical) mutual relations fully analyzed. The complete structural characterization of the two hydrated phases allows the use of accurate whole pattern profile‐fitting procedures for quantitative analyses of these drugs in polycrystalline, or even amorphous, matrices, opening the way to industrial process control and legal protection. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3641–3647, 2014